2018
DOI: 10.2495/air180211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Air Pollutant Emissions in a Wastewater Treatment Plant Using Dispersion Models

Abstract: The dispersion of air pollutants such as Ammonia (NH3) and Hydrogen Sulphide (H2S) emitted by a municipal wastewater treatment plant (WWTP) was studied for a period of over one year. The main intent was to support the environmental impact assessment focusing on the diffusion of annoying odours over surrounding areas during the regular activity of the sewage treatment facility. The adopted methodology consists in comparing, in three test cases, the performance of the Gaussian plume model AERMOD, an American Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The following are some of the air contaminants that emerge from wastewater ef luents and are simply releasable: 1) Hydrocarbons 2) Volatile compounds 3) Greenhouse gases 4) Airborne microbial contaminants 5) Nitrogen oxides and sulfur oxides 6) Heavy metals [24,32]. Wastewater treatment systems that employ air for separation (air lotation units), for oxygenation (aerobic biological processes), or pollutant removal (air stripping units) will eventually result in the release of VOCs and noxious gases from the wastewater at levels that are potentially harmful to human health [32].…”
Section: Resultsmentioning
confidence: 99%
“…The following are some of the air contaminants that emerge from wastewater ef luents and are simply releasable: 1) Hydrocarbons 2) Volatile compounds 3) Greenhouse gases 4) Airborne microbial contaminants 5) Nitrogen oxides and sulfur oxides 6) Heavy metals [24,32]. Wastewater treatment systems that employ air for separation (air lotation units), for oxygenation (aerobic biological processes), or pollutant removal (air stripping units) will eventually result in the release of VOCs and noxious gases from the wastewater at levels that are potentially harmful to human health [32].…”
Section: Resultsmentioning
confidence: 99%
“…[3,[11][12][13][14][15] Moreover, it was reported that the levels of pollutants are usually influenced by tank volume, the mechanical or technological approach used for the thickening of sludge, wastewater flow rates, daily working hours, wastewater temperatures, concentrations of pollutants in the wastewater entering the plant, and local wind speed. [16] In addition, agriculture activities, burning of agriculture wastes, and residential activities of nearby surrounding areas could affect the concentration levels of gaseous pollutants of Abu-Rawash WWTP.…”
Section: Monitoring Of Air Pollutantsmentioning
confidence: 99%
“…The detected high concentrations of particulate matter (PM 2.5 , PM 10 , and TSP) at the sludge thickening and dewatering process, and cyclone devices can be attributed to the aerobic and anaerobic digestion, mechanical thickening of sludge, sludge drying and flaring, and volatilization of chemicals from the liquid's surface. [4,[12][13][14][15][16] In addition, particulate matter concentrations were affected by the mechanical technology of sludge thickening, wastewater flow rates, daily working hours, concentrations of pollutants in the wastewater entering the plant and local wind speed. [18] In addition, agriculture activities, burning of agriculture wastes at residential areas surrounding the plant, dusty nature around the plant, and main highway road (Cairo-Alexandria desert road) near to the plant could be responsible for the increase in concentration levels of detected particulate matter.…”
Section: Gaseous Pollutantmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,9 The majority of previous studies regarding air pollutants dispersion, including NH 3 , have focused on pollution generated by industrial facilities such as wastewater treatment plants (WWTPs). 10,11 Additionally, AERMOD modeling of the dispersion of ammonia pollutants from urban traffic infrastructure has been considered. 12 Furthermore, municipal solid waste (MSW) landfills can contribute to unpleasant odors in urban areas.…”
mentioning
confidence: 99%